Efficacy of electroacupuncture in the treatment of peripheral neuropathy caused by Utidelone: Study protocol for a randomized controlled trial - Lu, Chao; Li, Guangliang; Deng, Dehou; Li, Rongrong; Li, Xiaoyu; Feng, Xukang; Wu, Taoping; Shao, Xiying; Chen, Weiji (Frontiers in Neurology, 2023)
Introduction: Utidelone(UTD1) is a new chemotherapeutic drug for recurrent or metastatic breast cancer. But it mainly leads to severe peripheral neuropathy(PN), causes numbness of the hands and feet, and causes significant pain in patients' life. Electroacupuncture(EA) is considered to be beneficial in improving PN and relieving numbness of the hands and feet. This trial aims to evaluate the therapeutic effect of EA on PN caused by UTD1 in advanced breast cancer patients. Methods and analysis: This study is a prospective randomized controlled trial. 60 PN patients caused by UTD1 will be randomly assigned to the EA treatment group and the control group in a ratio of 1:1. The patients in the EA treatment group will treat with 2Hz EA 3 times a week for 4 weeks. The patients in the control group will take Mecobalamin(MeCbl) tablets orally, 1 tablet each time and 3 times a day for 4 weeks. The main outcome measures will be the evaluation scale of peripheral neurotoxicity of chemotherapeutic drugs according to EORTC QLQ-CIPN20 and the peripheral neurotoxicity assessment rating according to NCI CTCAE V5.0. Secondary outcomes will be the quality of life scale according to EORTC QLQ-C30. The results will be evaluated at baseline, post-treatment phase, and follow-up. All major analyses will be based on the intention to treat principle. Ethics/dissemination: This protocol was approved by the Medical Ethics Committee of the Cancer Hospital of the University of Chinese Academy of Sciences (Zhejiang Cancer Hospital) on 26 July 2022. The license number is IRB-2022-425. This study will provide clinical efficacy data of EA in the treatment of PN caused by UTD1 and will help to prove whether EA is an effective and safe therapy. The study results will be shared with healthcare professionals through the publication of manuscripts and conference reports. Trial registration number: ChiCTR2200062741.